Pengaruh Perputaran Kas, Pertumbuhan Jumlah Nasabah Kredit Dan Non Performing Loan (NPL) Terhadap Profitabilitas Pada Lembaga Perkreditan Desa (LPD) Di Kecamatan Sukawati - Ni Putu Asriyanti; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2023)
Profitability becomes suitable to measure business performance, because profitability will reflect the capability on generating a profit or a measure of management’s effectiveness. This study about to determine effect of Cash Turnover, Growth in Number of Credit Clients and Non Performings Loan (NPL) at profitability. Study conducted on the Village Credits Institution at Sukawati District. The population are all VCIs in Sukawati District, 33 VCI. This study uses periodic data, namely LPD financial reports from 2019 to 2021. 99 financial statements from 33 active VCIs consisting of 3 years of financial statements are beinge examined using linear regression. Result concluds Cash Turnovers also Credit Clinets Growth give positive significant effect at Profitability variable. Meanwhile Non Performing Loan (NPL) gives negative significants effects on Profitability. This results could be considerated during the policy-making event to increase company profitability